1983
DOI: 10.1111/j.1476-5381.1983.tb11063.x
|View full text |Cite
|
Sign up to set email alerts
|

Increased 5‐HT2 receptor number in brain as a probable explanation for the enhanced 5‐hydroxytryptamine‐mediated behaviour following repeated electroconvulsive shock administration to rats

Abstract: 1 Following electroconvulsive shock (ECS) administration daily for 10 days there was an increase (35 %) in 5-hydroxytryptamine2 (5-HT2) receptor number in rat frontal cortex 24 h after the last ECS, compared with handled controls. A similar increase was seen after intermittent ECS administration (5 ECS over 10 days) given during halothane anaesthesia, compared with halothane-treated controls. The dissociation constant was also increased at this time. A single ECS had no effect. 2 Treatment of rats with pentyle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
1

Year Published

1984
1984
2010
2010

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 72 publications
(16 citation statements)
references
References 14 publications
1
14
1
Order By: Relevance
“…Repeated ECS results in an increase in the number of post-synaptic 5-HT2 receptors (Kellar etal., 1981;Green et al, 1983;Goodwin et al, 1984) and drugs shown to inhibit 5-HT release do increase cortical 5-HT2 receptor density in the cortex (Green et al, 1985;Gray et al, 1986). It is therefore possible that the changes seen in the current study and the 5-HT2 receptor change seen after repeated ECS are related.…”
Section: Discussionmentioning
confidence: 59%
“…Repeated ECS results in an increase in the number of post-synaptic 5-HT2 receptors (Kellar etal., 1981;Green et al, 1983;Goodwin et al, 1984) and drugs shown to inhibit 5-HT release do increase cortical 5-HT2 receptor density in the cortex (Green et al, 1985;Gray et al, 1986). It is therefore possible that the changes seen in the current study and the 5-HT2 receptor change seen after repeated ECS are related.…”
Section: Discussionmentioning
confidence: 59%
“…Thus, the 5-HTzA receptor-mediated hyperactivity syndrome in rats was enhanced after chronic ECS (Evans et al, 1976), a finding matched by increased binding at postsynaptic 5-HT2 receptor sites in cerebral cortex (Kellar et al, 1981;Vetulani et al, 1981;Green et al, 1983;Burnet et al, 1995). Behaviours mediated by the 5-HT1A receptor, however, were not uniformly modified by ECS.…”
Section: Introductionmentioning
confidence: 81%
“…In this regard it showed a similar profile to repeated ECS which enhances 5-HTmediated behaviour in mice not only when given daily but also when given 5 times over 10 days (Lebrecht & Nowak, 1980;Green etal., 1983b). A further similarity came with the observation that repeated progabide administration increased the number of 5-HT2 binding sites, since this also occurs after repeated ECS (Vetulani et al, 1981;Kellar et al, 1981;Green et al, 1983a) and data suggest that the increased behaviour response and increased in 5-HT2 receptor number are associated (Green et al, 1983a). An increase in 5-HT2 receptor number in frontal cortex after repeated progabide administration has also been reported to occur in rats (Langer et al, 1984).…”
Section: Discussionmentioning
confidence: 99%
“…Rats which appears to be responsible for the enhanced show an enhanced hyper-activity response to 5-hybehavioural response (Green et al, 1983a). droxytryptamine (5-HT) agonists whilst mice show an Mice and rats also show an enhanced locomotor increased head-twitch response (Evans et al, 1976; response to dopamine agonists (Modigh, 1975;Evans Green et al, 1977;Lebrecht & Nowak 1980;Green et et al, 1976;Deakin et al, 1981) although there does al., 1983b).…”
Section: Repeated Administration Of Electroconvulsive Shockmentioning
confidence: 99%